When You Praise the Ruler, Do not Hesitate to Boast Your Own Talent – Analysis of the Poem Heraclias, Book I, Verses: 1–139 of George of Pisidia - Magdalena Samoń-Trzos (Classica Cracoviensia, 2024)
The poems of George of Pisidia – the court poet of the Emperor Heraclius – are not only an important historical source for the reign of this Byzantine ruler, but also an expression of the extraordinary erudition and talent of their author. The subject of this article is an analysis concerning a fragment of one of them – Heraclias. In this epic, which is a praise of the emperor’s reign, the poet with true virtuosity weaves references to the traditions and culture of pagan and Christian antiquity into the historical narrative. Based on rhetorical recommendations, he gives his poem a laudatory character. Pisides creates an extraordinary, surprisingly coherent work. The poet’s erudition is revealed not only by the content but also by the compositional devices of his works.